Prophetic Medicine as Indonesian Herbal Branding: (Study on CV Naturonal Mediatama Indonesia) - Suharti, Bangun; Suciska, Wulan; Firdaus, Ferry; Setyowati, Puspandari (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
The herbs used by the community are still identical to ancestral heritage, unhygienic and impractical jamu gendong. Herbs are not yet considered part of the prophet's ittiba. The purpose of this research is to find out how the digital integrated marketing strategy in branding Indonesian herbs by CV Naturonal Mediatama Indonesia. This research was conducted with observation and documentation studies on digital media used for branding herbal products of CV Naturonal Indonesia. The conclusion of the research shows that digital media is used massively and integrated as a means of branding Indonesian herbal products. The branding image of Indonesian herbs to be built is: herbs as a treatment ala tibbun nabawi / prophetic medicine (treatment ala prophet Muhammad SAW), which is rational, scientific, standardized sanadnya, easy and practical use, not inferior to chemical drugs.